2010
DOI: 10.1007/s00592-010-0226-0
|View full text |Cite
|
Sign up to set email alerts
|

Significance of serum microRNAs in pre-diabetes and newly diagnosed type 2 diabetes: a clinical study

Abstract: To explore the clinical significance of seven diabetes-related serum microRNAs (miR-9, miR-29a, miR-30d, miR34a, miR-124a, miR146a and miR375) during the pathogenesis of type 2 diabetes (T2D), 56 subjects were recruited to this study: 18 cases of newly diagnosed T2D (n-T2D) patients, 19 cases of pre-diabetes individuals (impaired glucose tolerance [IGT] and/or impaired fasting glucose [IFG]) and 19 cases of T2D-susceptible individuals with normal glucose tolerance (s-NGT). Serum miRNAs were determined by real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
343
1
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 484 publications
(368 citation statements)
references
References 41 publications
16
343
1
8
Order By: Relevance
“…The observation of the deregulation of miRNA profiles in different biological fluids of diabetic patients compared with healthy controls was the first evidence supporting the idea that miRNAs could be biomarkers of the diabetic disease (Table 1). Indeed, a differential miRNA profile between type 2 diabetic patients and healthy controls was found in whole blood [20,21], serum [22][23][24][25][26], plasma [27][28][29][30][31][32][33] and plasma exosomes [34]. Studies revealed a different miRNA pattern in serum of type 1 diabetic patients compared with healthy individuals [35], as well as in plasma [36,37] and urine [36].…”
Section: Circulating Mirnas As Biomarkers Of the Diabetic Conditionmentioning
confidence: 99%
See 4 more Smart Citations
“…The observation of the deregulation of miRNA profiles in different biological fluids of diabetic patients compared with healthy controls was the first evidence supporting the idea that miRNAs could be biomarkers of the diabetic disease (Table 1). Indeed, a differential miRNA profile between type 2 diabetic patients and healthy controls was found in whole blood [20,21], serum [22][23][24][25][26], plasma [27][28][29][30][31][32][33] and plasma exosomes [34]. Studies revealed a different miRNA pattern in serum of type 1 diabetic patients compared with healthy individuals [35], as well as in plasma [36,37] and urine [36].…”
Section: Circulating Mirnas As Biomarkers Of the Diabetic Conditionmentioning
confidence: 99%
“…Its altered expression in islets and/or pancreas has been observed in animal models with a predisposition to type 2 diabetes [52] and overt diabetes [7]. While miR-375 expression is not significantly augmented in human islets from glucose intolerant donors [53], increased levels have been observed in the pancreas [54] and blood of type 2 diabetic patients [22,33]. Given that miRNAs have been described as being responsive to cellular and extracellular stress and to be used by cells to adjust changes in their environment, it is conceivable that, under conditions of harsh stress, such as type 2 diabetes, miR-375 is increased, while under circumstances of mild stress, such as glucose intolerance, its expression remains in the normal range.…”
Section: Circulating Mirnas As Biomarkers Of the Disease Processmentioning
confidence: 99%
See 3 more Smart Citations